A Metallaphotoredox Strategy for the Cross‐Electrophile Coupling of α‐Chloro Carbonyls with Aryl Halides. (5th September 2019) - Chen, Tiffany Q.; MacMillan, David W. C.
Abstract: Here, we demonstrate that a metallaphotoredox‐catalyzed cross‐electrophile coupling mechanism provides a unified method for the α‐arylation of diverse activated alkyl chlorides, including α‐chloroketones, α‐chloroesters, α‐chloroamides, α‐chlorocarboxylic acids, and benzylic chlorides. This strategy, which is effective for a wide variety of aryl bromide coupling partners, is predicated upon a halogen atom abstraction/nickel radical‐capture mechanism that is generically successful across an extensive range of carbonyl substrates. The construction and use of arylacetic acid products have further enabled two‐step protocols for the delivery of valuable building blocks for medicinal chemistry, such as aryldifluoromethyl and diarylmethane motifs. Abstract : Auf Knopfdruck : Die metallaphotoredoxkatalysierte Kreuzkupplung von Elektrophilen liefert eine einheitliche Methode zur α‐Arylierung diverser aktivierter Alkylchloride. Diese Strategie ist äußerst effektiv für eine Vielzahl von (Hetero‐)Arylbromide unter milden Bedingungen. Die Anwendung dieses Protokolls wird für Bausteine für die medizinische Chemie, wie Aryldifluoromethyl‐ und Diarylmethan‐Motive, demonstriert.